Numerical study of flow behavior in a cavitation tunnel using RANS with Scale-Adaptive Simulation (SAS) turbulence model in an OpenFOAM framework. Issue 1 (June 2021) - Hidalgo, V; Suárez, G; Erazo, J; Puga, D; Márquez, D; Benavides, I; Cando, E; Valencia, E; Luo, X
Abstract: The present paper focuses on the study of flow through a cavitation Venturi tunnel. Motivated by the results obtained in the studies of "Simultaneous observation of cavitation structures and cavitation erosion" and "Combined numerical and experimental investigation of the cavitation erosion process" by Dular et al. A structured mesh based on previous studies has been generated using the free software GMSH. The numerical study was performed using the Navier-Stokes equations with RANS approximation. For that, the k − ω − SST SAS turbulence model and the implemented Zwart-Gerber-Belamri have been applied in OpenFOAM. The results show that the phenomena in a vapor volume fraction where the formation, growth, detachment and collapse of the cavitation cloud can be appreciated. These results agree with the aforementioned studies. Furthermore, the results show the peak pressure formation corresponding to the detachment and collapse of the cloud during the cavitation cycle, which is the main reason for erosion. It is concluded that the model satisfactorily predicts the phenomena behavior on a Δ t = 9 × 10 − 6[s] being suitable to capture adverse pressure gradients.